MODAL SOSIAL BEAS PERELEK : ANALISIS KEBERLANJUTAN DAN STRATEGI ELABORASI DI ERA MILENIAL - Nurul Aidatul Fitriah; Brilianza Azharul Mujahidin; Adi Nugraha; Wiwiek Rindayani (Jurnal Indonesia Sosial Sains, 2020)
Indonesia is a country with high social capital. However, with the times and the high flow of globalization, it has caused the fading of the spirit of mutual cooperation and concern for others.. In West Java, reviving the beas perelek is a solution. However, a question arises whether this tradition can be applied in the era of the millennial generation as it is today. The purpose of this research is to describe the implementation and to analyze the potential for sustainability of the prize fund in West Java society and to provide recommendations for elaboration strategies in the application of the prize fund in the millennial era. This research method is qualitative with the tectic of collecting data from literature studies. The sustainability analysis technique uses the rapfish-MDS method and the SWOT method to formulate a free elaboration strategy for men in the millennial era. The results showed the continuity of the free tradition in the good category with continuing status. To improve its implementation, it is necessary to carry out an elaboration strategy so in accordance  with the era.